2007
DOI: 10.1111/j.1469-0691.2006.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour and Chlamydia trachomatis infections in German female urban adolescents, 2004

Abstract: This ad-hoc observational study, conducted in the metropolitan area of Berlin during 2004, revealed that the prevalence of Chlamydia trachomatis (CT) infections in female urban adolescents self-presenting at their gynaecologist without (n=397) or with (n=124) symptoms of CT infection was 5.5% (95% CI 3.7-8.2%) and 9.7% (95% CI 5.6-16.2%), respectively. The prevalence of CT infection was significantly dependent on the number of lifetime sexual partners. Condom use was inconsistent, and lack of knowledge about C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…We found that most young women are not knowledgeable about Chlamydia, and many do not distinguish between screening for Chlamydia and screening for other, less prevalent STDs. These findings are representative of the generally low levels of chlamydia knowledge in the United States and abroad, [10][11][12][13] underscoring the importance of raising basic awareness in order to promote screening uptake and acceptability. 8 Young women's discussions suggested they have low levels of perceived susceptibility to STDs.…”
Section: Discussionmentioning
confidence: 65%
“…We found that most young women are not knowledgeable about Chlamydia, and many do not distinguish between screening for Chlamydia and screening for other, less prevalent STDs. These findings are representative of the generally low levels of chlamydia knowledge in the United States and abroad, [10][11][12][13] underscoring the importance of raising basic awareness in order to promote screening uptake and acceptability. 8 Young women's discussions suggested they have low levels of perceived susceptibility to STDs.…”
Section: Discussionmentioning
confidence: 65%
“…Most other population-based studies were performed in sexually experienced participants aged 18-24 years, showing among women a prevalence of 3.6% (95% CI: 1.9-6.8) in France, 4.7% (95% CI: 2.5-8.5) in Slovenia and 3.0% (95% CI: 1.7-5.0) in the UK [12,13,23]. In an observational study performed in 2004 among sexually experienced females aged 14-20 years in Berlin, Germany, CT-positivity of 6.5% (95% CI: 4.7-9.0) was found [24]. In a study performed in 2008-09 in a mid-sized town in Germany, a prevalence of 4.2% was found in 14-19 year-old females and was associated with an early age of first sexual contact and increasing number of lifetime sexual partners [25].…”
Section: Discussionmentioning
confidence: 98%
“…One explanation could be that young girls who take the pill no longer use condoms [24], as pregnancy prevention has been frequently reported as a major reason for condom use in young females. In the United States, an increase in oral contraceptive intake from 8% in 9th-grade females to 30% in 12th-grade females was found as was a concomitant decrease in condom use from 56% to 49% in those sexually active females [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that young people have a poor awareness of the link between STIs and infertility [19,23,24] whereas others have reported the opposite [25-27]. This disparity may primarily be due to the differences in age and educational levels of the samples, and the different methods of data collection.…”
Section: Discussionmentioning
confidence: 99%